2014
DOI: 10.1051/radiopro/2014015
|View full text |Cite
|
Sign up to set email alerts
|

Use of personal radiation protection tools and individual dosimetric monitoring in a sample of interventional cardiologists in France, 2005–2009

Abstract: -Interventional cardiologists (ICs) are repeatedly exposed to scattered ionising radiation during the cardiac procedures they perform, and radiation protection is an important issue for these medical professionals. The use of radiation protection tools is particularly relevant to this population. SISERI (Système d'Information de la Surveillance de l'Exposition aux Rayonnement Ionisants, that is, an information system for monitoring exposure to ionising radiation) is a register that stores personal dosimeter re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Furthermore, given that non-significant results are less likely to be reported [ 114 ], it can be assumed that the dose–response relationship between occupational medical IR exposure and cancer biomarkers is poorly understood [ 27 , 64 , 71 , 74 ]. Issues associated with dose records include for example underestimation of dose when personal badges are not properly worn as observed in cardiologists studies [ 115 ], which could affect corresponding dose-response estimates [ 116 ]. However, IR-exposure assessed by the duration of employment as proxy did not show more conclusive results [ 24 , 30 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, given that non-significant results are less likely to be reported [ 114 ], it can be assumed that the dose–response relationship between occupational medical IR exposure and cancer biomarkers is poorly understood [ 27 , 64 , 71 , 74 ]. Issues associated with dose records include for example underestimation of dose when personal badges are not properly worn as observed in cardiologists studies [ 115 ], which could affect corresponding dose-response estimates [ 116 ]. However, IR-exposure assessed by the duration of employment as proxy did not show more conclusive results [ 24 , 30 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, our results may be underestimated because they are contingent on the acceptance of the dosimeter by the medical staff, which is not always the case during radiation procedures [19]. Moreover, it was not possible to distinguish the true decrease of doses from a lack of exposure due to change in the work, such as nurses becoming team leaders during the study period.…”
Section: Discussionmentioning
confidence: 86%
“…In order to ensure reliable measurement of exposure, IR-exposed workers are required to wear a personal dosimeter during the course of their work [10]. However, several studies have shown that HW do not always comply with the rules governing dosimeter wearing [11,12].…”
Section: Introductionmentioning
confidence: 99%